'Affection in Education': Edward Carpenter, John Addington Symonds and the politics of Greek love - Quinn, J; Brooke, C (2011)
The paper examines Edward Carpenter's 1899 essay on education that defended the value of powerful same-sex attachments, either between older and younger boys or between teachers and pupils, in the context of Victorian ideologies of same-sex affection. Linda Dowling has described how 'a homosexual counterdiscourse able to justify male love in ideal or transcendental terms' was fashioned out of the discourse of Greek studies in 19th-century Oxford by Walter Pater, Oscar Wilde and the Uranian poets. We argue that Carpenter's position in both 'Affection in Education' and his pamphlet on Homogenic love is best interpreted not in terms of this particular counterdiscourse so much as in light of John Addington Symonds' sharp political reaction against it, a reaction that was grounded in recent historical scholarship on the ancient Greeks and which rejected the idealisation of intellectualised, aristocratic boy-love in favour of a vision of egalitarian sexual relationships between men, and which was, in Carpenter's own case, very closely associated with his own ideals of social and political progress. © 2011 Copyright Taylor and Francis Group, LLC.